On a Ahlfors-Denjoy Type Result - Contreras J., Roberto; Bezanilla L., Arnoldo (Communications in Mathematics and Applications, 2014)
The present paper is concerned with the general problem of extending the classical theory of analytic functions of a Complex variable. The asymptotic behavior of power series defined on a Banach algebra with multiplicative functional or with a Gelfand theory is analyzed here and some lower estimates for the order of power series defined on this Banach algebras are given here.